Aceh Besar بالعروض التقديمية في تعليم القواعد النحوية بمعهد دار الإحسان Numbered Head Togetherتطبيق أسلوب - Rizqullah, Rifqi Rifqi; Hilmi, Hilmi; Badruzzaman, Badruzzaman (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
The study of grammar at Darul Ihsan Boarding School addresses several issues identified by the researcher, including a decline in student enthusiasm, discomfort, lack of interest in the subject matter, and weak collaboration among students. Additionally, teachers face the challenge of insufficient time to present the material comprehensively and adequately, leading to a decrease in students' academic achievement. This research aims to explore the implementation of the Numbered Heads Together (NHT) method using presentations in grammar instruction and to evaluate its effects and students' responses. The research employs an action research methodology, targeting a population of 1,307 students. The sample consists of 20 first-grade high school students from class 1C. The researcher utilized observation sheets, questionnaires, and tests for both the first and second phases as research instruments. The findings indicate that the teaching and learning process during the first phase, according to the implementation plan, achieved a rate of 58% (acceptable), while the second phase achieved a rate of 92.3% (very good). Students' proficiency in grammar improved, with an average score of 58 in the first phase (acceptable) and 74.5 in the second phase (good). Additionally, 94.5% of students responded positively, with only 5.5% negative feedback, indicating a generally positive student response.